BRANDING IMAGE MANAGEMENT IN IMPROVING THE COMPETITIVENESS OF EARLY CHILDREN'S EDUCATION IN THE SOCIETY 5.0 ERA - Sholihah, Chodijatus (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to determine the increase in the competitiveness of early childhood education institutions by involving branding image management in the era of society 5.0. This research is qualitative with the type of case study conducted at PAUD AL-Choliliyah Karanganyar Paiton Probolinggo. The sources of informants in this study were PAUD heads, teachers, and student guardians. Then to select and determine the informants in this study, researchers used a purposive sampling technique. Data collection techniques in this study used content/document analysis techniques, in-depth interviews, and events/observations. The method used to check the validity of the data is the triangulation method. The data analysis technique used in this research is interactive model analysis. The stages in analyzing the data in this study are data reduction, data presentation, and conclusion. This study's results indicate that PAUD AL-Choliliyah involves branding image management in increasing the competitiveness of institutions in the era of society 5.0. Second, the control of the branding image management strategy is carried out using; Problem Mapping, Branding Image Implementation, Result Branding Image and Continuous Improvement.